Aktivitas Larvasida Ekstrak Daun Bintaro (Cerbera odollam Gaertn.) Terhadap Larva Nyamuk Aedes aegypti - Virsa Handayani; Rezki Amriati Syarif; Aktsar Roskiana Ahmad; Andi Afifah Amdar (Jurnal Fitofarmaka Indonesia, 2023)
Bintaro Leaf (Cerbera odollam Gaertn) contains alkaloids, flavonoids, saponins and tannins that have the potential as larvicides. The study aimed to determine the mortality rate of Aedes aegypti mosquito larvae after administration of Bintaro leaf extract as indicated by the LC50 value. The extract was obtained by maceration method. The yield of Bintaro Leaf (Cerbera odollam Gaertn)extract was 6.03%. This study used 180 mosquito larvae (Aedes aegypti) instar III, divided into test solutions made with 4 concentrations (10,000 ppm, 1000 ppm, 100 ppm and 50 ppm), positive control using Abate and negative control using Aquadest. Observations were made after 24 hours of treatment. The results of the larvacide test showed that the Bintaro leaf extract was effective as a larvicidal as indicated by the LC50 value of 21.170 g/mL 1000 g/mL.